Strategic Leadership in Indonesian Maritime Security and Its Relationship with the World Maritime Axis - Cecep Hidayat,; Syaiful Anwar,; T. S. L. Toruan,; Luhut Simbolon, (RES MILITARIS, 2023)
Indonesia's geopolitical and geostrategic position certainly provides an opportunity for this archipelagic country to not only serve as a global economic pathway but also an international maritime security pathway which will ultimately position Indonesia as having a relatively high advantage and dependence on the maritime sector. Until now, the development of the national maritime sector still faces a number of obstacles. In order to be able to transform into a maritime country, Indonesia must have the capability to optimize the maritime area not only as economic centrality an sich, but also as a basis for the development of military strength plus defense. With Indonesia's geostrategic and geoeconomic position, Jokowi understands that it can be realized into a PMD (Poros Maritim Dunia/World Maritime Axis) policy. This is an important step in efforts to synergize strategies to improve the economy and on the other hand also directly strengthen Indonesia's maritime defense and security. This study will try to explain strategic leadership in the context of Indonesian maritime security. This research took the discussion of the idea of PMD. There are at least three elements that ideally the Indonesian government needs to have in the PMD idea so that it can properly deal with maritime security issues. By using qualitative research methods, this article tries to answer the question, three variables are lacking in the PMD idea, where these three are basic elements for countries to deal with maritime security issues as part of maritime policy, such as the case of Indonesia, as a country that wants to developing a maritime-based economy. Findings from this study discuss Indonesia as a World Maritime Axis, Indonesian Maritime Doctrine, Indonesian Sea in the Perspective of MDA (Maritime Domain Awareness), and Indonesia's Maritime Security Strategy through the World Maritime Axis. From the discussion and findings of this study, it can be concluded that efforts to realize the nation's two strategic interests, namely the economy and security, were carried out by Jokowi through the PMD policy doctrine. Economic development requires defense and security stability, while defense forces require budget allocation support and economic capacity.